THE RECONCEPTUALISATION OF KNOWLEDGE BASE IN THE PRE-SERVICE TEACHER EDUCATION CURRICULUM: TOWARDS ELF PEDAGOGY - Sakhiyya, Zulfa; Agustien, Helena I.R.; Pratama, Hendi (Universitas Pendidikan Indonesia, 2018)
This article examines ?what will be taught? or the knowledge base demonstrated in the English language teacher education curricula by using the framework of English as a Lingua Franca. The need for enhancing the professionalism of English teachers in the ascendancy of English as a Lingua Franca (ELF) in Indonesia demonstrates a critical point where pre-service teacher education holds strategic roles. This epistemological turn needs to ensure that the teachers are devised with knowledge base as well as contextual approach suited to each particular educational environment. Fifteen Indonesian pre-service teacher education programmes were randomly selected and meta-analysed to aggregate the extent of reconceptualisation of the knowledge base provision by focusing on the curricula?s emphasis (linguistics and/or language proficiency) and the integration of socio-cultural perspective. Although these curricula cannot wholly represent cultural responsiveness and pedagogical practices, they could serve as sites concerning the values and knowledge held as important in the institution. We argue that there is a need to place a greater emphasis on the language proficiency that matches the ELF paradigm, as well as to reconceptualise the knowledge base to respond to the diverse Indonesian socio-cultural realities encountered by the recontextualising agents, the teachers. The reconceptualisation of knowledge base would foster greater awareness of sociocultural relativity and learning expectations of teaching ELF situated in the Indonesian educational context.